DIGITAL MARKETING STRATEGIES BASED ON CONSUMER PERCEPTION OF THE BRAND. MAGAZIA MORĂRIȚEI CASE STUDY, IASI, ROMANIA - Alexandra Raluca JELEA; Ioan Sebastian BRUMĂ (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
In the global agricultural landscape, small producers play a crucial role in preserving tradition, fostering resilience, and driving innovation. Despite operating on modest plots of land, they contribute significantly to feeding communities, conserving biodiversity, and sustaining rural economies. This study goes deeper into the world of small producers, focusing on "Magazia Morăriței", a well known brand, renowned for producing ecological bread and other bakery products since the 1990s.Through a mixed-methods approach involving surveys and psychological tests, the study explores consumer perceptions, online engagement, and buying behaviours associated with the brand. The findings reveal that consumers perceive Magazia Morăriței positively, associating it with strong brand personality traits, particularly reflecting the owner's image as a resilient businesswoman. Furthermore, consumers strongly associate the brand with traditional values, quality, and ecological certifications, driving their purchasing decisions. While the brand maintains a significant online presence, there exists a gap between online engagement and physical store visits, suggesting opportunities for improvement in bridging this divide. Moreover, the study unveils the neural networks formed in consumers' minds, highlighting core associations such as good bread, quality, tradition, and yeast bread, which reflect the brand's strong connection with its core products. Additionally, the brand's emphasis on ecological certifications and locally sourced products resonates with consumers, influencing their buying behaviours. Overall, this study underscores the importance of understanding consumer perceptions, leveraging online platforms effectively, and emphasizing brand values to drive consumer engagement and purchasing decisions. By addressing these insights, brands like Magazia Morăriței can enhance their market position and strengthen relationships with consumers, contributing to the sustainable growth of small producers in agriculture.